2022
DOI: 10.1007/s10433-022-00691-5
|View full text |Cite
|
Sign up to set email alerts
|

The health advantage of volunteering is larger for older and less healthy volunteers in Europe: a mega-analysis

Abstract: There is a vast literature on the health benefits associated with volunteering for volunteers. Such health advantages are likely to vary across groups of volunteers with different characteristics. The current paper aims to examine the health advantages of volunteering for European volunteers and explore heterogeneity in the association between volunteering and health. We carry out a mega-analysis on microdata from six panel surveys, covering 952,026 observations from 267,212 respondents in 22 European countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 61 publications
(75 reference statements)
2
7
0
1
Order By: Relevance
“…Besides the motivation to donate time to the social economy, there are several barriers to volunteering (McKenzie et al, 2021 ; Southby et al, 2019 ; Sundeen et al, 2007 ). Although several studies mention that volunteering can bring benefits to the various stakeholders — volunteers, the organisation and its public, as well as the community itself (Ganesh & Mcallum, 2012 ; Handy & Srinivasan, 2004 ; Wit et al, 2022 ) —, not all individuals are equally predisposed to volunteering (Macduff et al, 2009 ; Netting et al, 2005 ). Efficient management of non-profit organisations and volunteer recruitment critically implies understanding both the motivations to engage in social economy activities and the barriers that hinder such involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the motivation to donate time to the social economy, there are several barriers to volunteering (McKenzie et al, 2021 ; Southby et al, 2019 ; Sundeen et al, 2007 ). Although several studies mention that volunteering can bring benefits to the various stakeholders — volunteers, the organisation and its public, as well as the community itself (Ganesh & Mcallum, 2012 ; Handy & Srinivasan, 2004 ; Wit et al, 2022 ) —, not all individuals are equally predisposed to volunteering (Macduff et al, 2009 ; Netting et al, 2005 ). Efficient management of non-profit organisations and volunteer recruitment critically implies understanding both the motivations to engage in social economy activities and the barriers that hinder such involvement.…”
Section: Introductionmentioning
confidence: 99%
“… When income increases, giving does not increase proportionally (Neumayr & Pennerstorfer, 2021).  Among the elderly, volunteering maintains and may even improve health (De Wit, Qu, & Bekkers, 2022).  Among those out of work, however, volunteering does not improve well-being (Kamerāde & Bennett, 2018).…”
Section: Recent Research Areasmentioning
confidence: 99%
“…According to AA, one of the activities of seniors is volunteering. Research shows that volunteering, as a form of social commitment and socialisation, has positive health benefits to individuals, especially the more sensitive people, and affects their well-being [66,67]. Tanskanen et al [68] indicated that older people who help relatives and friends by giving informal monetary help and charitable donations, often participate and are more likely to engage in pro-social activity, volunteering and charity.…”
Section: Participation Of Seniors In Aa-literature Reviewmentioning
confidence: 99%